Analysis of Factors Related to Healing of Perineal Stitch Wounds in Postpartum Mothers - Pratiwi, Cici; Indriani, Putu Lusita Nati; Dhamayanti, Reffi; Wiranti, Bhakti; Anggraini, Arie; Rahmawati, Eka (International Journal of Health Sciences, 2024)
Perineal pain arises due to tearing or laceration of the perineum during the birth process due to severed tissue, which stimulates the hypothalamus to release pain receptors in the perineal area. Caring for perineal wounds, one of the important things is carrying out vulva hygiene. The benefits of vulva hygiene are keeping the vagina and the surrounding area clean and comfortable, preventing the appearance of vaginal discharge, unpleasant odors and itching and maintaining a constant vaginal pH. Vulva care is carried out every morning and evening before bathing, after urinating, defecating and if the postpartum mother feels uncomfortable because the lochea smells or there are complaints of pain. As a result of poor perineal wound care, the condition of the perineum affected by lochea becomes moist and will greatly support the growth of bacteria which causes infection in the perineum which can hinder the wound healing process. The postpartum period is an important thing to pay attention to, where the recovery of reproductive organs that experience changes during the pregnancy process occurs. Knowing the Factors Associated with the Healing of Perineal Suture Wounds in Postpartum Women at the Ujungpandang Baru Community Health Center. This study used a descriptive method. Mobilization and personal hygiene factors were related to perineal suture wound healing and tradition was not related to perineal suture wound healing.